Sight Loss and Minimum Living Standards : the additional costs of living for people of working age who are severely sight impaired and for people of pension age with acquired sight impairment /: the additional costs of living for people of working age who are severely sight impaired and for people of pension age with acquired sight impairment. (January 2016) - Hill, Katherine, 1966-; Marshall, Lydia; Hirsch, Donald; Padley, Matt
No abstract available